Improving Student's Listening Skills Using Tiktok at SMP Swasta Amalyatul Huda Medan - Emsi Feni SP Br Perangin angin; Mey Clara Anrefika Silaban; Resperdiana Purba (Jurnal Ilmiah Profesi Pendidikan, 2021)
The importance of applying English lessons as the primary learning from an early age is to improve students' ability to speak English, which can be used in international communication in the future. One of the critical lessons is listening, improving students' listening skills is very important, where students' listening ability in Swasta Amalyatul Huda Junior High School is still low. So this study aims to improve students' listening skills by using TikTok media. The method used is Classroom Action Research (CAR) by conducting two experiments, namely, Cycle I and Cycle II. The research instrument uses observation sheets, interviews, and questionnaires. The sample of this study was taken from 22 students in grade 7 at Swasta Amalyatul Huda junior high school. Based on the research that has been done, the results found by the researchers are the average values found from the two cycles, namely, Cycle I with an average value of 64.5 with a sufficient predicate (C), while in Cycle II, the average value is 78.2 with a good predicate ( B). Based on the study results, it shows that TikTok media can improve students' English listening skills.